1, 2, 4-Triazole Schiff base directed synthesis of polynuclear iron complexes: Investigating the magnetic properties going from a dimer to a 1D chain to a 3D framework. (1st November 2018) - Li, Ai-Min; Rentschler, Eva
Graphical abstract: A series of polynuclear iron complexes was synthesized and characterized, covering from a dimer to 1D chain to 3D framework. All compounds show antiferromagnetic exchange interaction between the adjacent Fe centers. Abstract: Based on two functionalized Schiff base ligands 4-(1 H -imidazol-5-ylmethylene-amino)-4 H -1, 2, 4-triazole (imztrz) and 4-( p -tolylidene-amino)-4 H -1, 2, 4-triazole (toltrz), a series of three triazole based polynuclear Fe complexes has been prepared. Compounds [Fe II (toltrz)2 (C2 O4 )]·10H2 O n (1 ) and [Fe II (5-imztrz)(C2 O4 )]·2H2 O n (2 ) are oxalate bridged Fe II complexes with1 showing a linear 1D chain structure and2 exhibiting a zigzag chain based 3D interpenetrating framework. Both structures show rather big voids in the 3D architecture (∼15% of the crystal volume). Compound (5-imztrzH)2 [Fe III 2 (cit 4− )2 (H2 O)2 ]·6H2 O (3 ) is a binuclear Fe III complex bridging by two citrate ligands to form a face-shared centrosymmetric structure. Magnetic susceptibility measurements indicate that all three compounds show weak antiferromagnetic exchange interaction between the adjacent Fe centers.